Bioprospecting macroalgae, marine and terrestrial invertebrates & their associated microbiota - Costa-Lotufo, Leticia Veras; Colepicolo, Pio; Pupo, Mônica Tallarico; Palma, Mario Sergio [UNESP] (FapUNIFESP (SciELO), 2022)
The present review aims the discussion of the impact of the bioprospection initiative developed by the projects associated to BIOprospecTA, a subprogram of the program BIOTA, supported by FAPESP. This review brings a summary of the main results produced by the projects investigating natural products (NPs) from non-plants organisms, as examples of the success of this initiative, focusing on the progresses achieved by the projects related to NPs from macroalgae, marine invertebrates, arthropods and associated microorganisms. Macroalgae are one of the most studied groups in Brazil with the isolation of many bioactive compounds including lipids, carotenoids, phycocolloids, lectins, mycosporine-like amino acids and halogenated compounds. Marine invertebrates and associated microorganisms have been more systematically studied in the last thirty years, revealing unique compounds, with potent biological activities. The venoms of Hymenopteran insects were also extensively studied, resulting in the identification of hundreds of peptides, which were used to create a chemical library that contributed for the identification of leader models for the development of antifungal, antiparasitic, and anticancer compounds. The built knowledge of Hymenopteran venoms permitted the development of an equine hyperimmune serum anti honeybee venom. Amongst the microorganisms associated with insects the bioprospecting strategy was to understand the molecular basis of intra-and interspecies interactions (Chemical Ecology), translating this knowledge to possible biotechnological applications. The results discussed here reinforce the importance of BIOprospecTA program on the development of research with highly innovative potential in Brazil.
Bioprospecção de macroalgas, invertebrados marinhos e terrestres e microbiota associada
Keywords: arthropods; bioeconomy; biological active compounds; insects; microbiota; Natural products